Causal effects and functional mechanisms of the Internet on residents' physical fitness-An empirical analysis based on China family panel survey - Zhang, Long; Lu, Chuntian; Yi, Cuixia; Liu, Zhipeng; Zeng, Yuhua (Frontiers in Public Health, 2023)
Introduction Physical fitness is an essential part of a healthy lifestyle that concerns the overall health of the nation. Research on the relationship between the Internet and physical fitness has long been caught in the dilemma of “media mobilization” and “media suppression,” and previous studies have rarely examined the causal relationship and functional mechanism. Methods This study selected the data of 23,989 samples successfully followed in all three surveys of the China Family Panel Survey (CFPS) from 2014 to 2018 to explore the correlation and causal inference between the Internet and physical fitness by using the Time Fixed Effects Model and cross-lagged models, respectively; meanwhile, the data of 24,687 samples in CFPS 2020 to examine the functional mechanism of the Internet's effect on residents' physical fitness behavior by the KHB method. Results We obtained three valuable conclusions as follows: First, there is a significant correlation between the Internet and physical fitness behavior. Second, the Internet use is the cause for the increase in fitness frequency, and there is a rival relationship between Internet duration and fitness time. Third, under regular prevention and control of the COVID-19 epidemic, social capital and health risk perceptions are the functional mechanisms of the Internet influencing fitness behavior, and the mediating effect of psychological health risk perceptions is higher than that of social capital. Discussion It's necessary to create an intelligent, informative, and digital sports public service system by enriching and optimizing sports media and facilitating the Internet to serve residents' physical fitness better. The new concept of “Internet plus Fitness” will be of great significance in the implementation of the “Healthy China Initiative.”